Assessing the laboratory mass rearing of Predator Beetle Rhizophagus grandis Gyll. (Coleoptera: Monotomidae) - Özcan, Gonca Ece; Eroğlu, Mahmut; Alkan Akinci, Hazan (Springer Science and Business Media LLC, 2021)
The aim of this study was to determine the progeny production of predator beetle Rhizophagus grandis (Gyllenhal) (Coleoptera: Monotomidae) under laboratory conditions. Different numbers of male and female predators introduced into breeding logs and the numbers of new progenies and their sex ratios were determined in the early and late spring periods. A total of 8776, 13,402, 5742 and 7864 R. grandis individuals were reared in 60, 109, 128 and 56 breeding logs in four consecutive years, respectively. Of the prepupae that have dropped from breeding logs to enter the sand in experimental basins, 81.4 % of them have emerged as adults at the end of the experimental periods. The average number of R. grandis per log was 146.2, 123, 44.9 and 140.4 according to experimental years, and 181.7 and 93.2, 123, 62.4 and 32.9, 163.8 and 101.5 according to the early and late spring periods in the experimental years, respectively. In the second year of the experiments, only early spring rearings have been performed that have yielded 123 R. grandis per log on average. Progeny production of a female R. grandis was 18.3, 18.7, 5.8 and 17.6 on average, 2004, 2005, 2006 and 2007 respectively. Different numbers of predator females and males were used in early and late spring experiments in the study. Progeny production was higher in early spring when the experiments were performed with 6 females and 2 males. Of the 35,784 R. grandis individuals that were obtained from the experiment, 16.4 %, 28.3 % and 55.3 % were collected from the first, second and third part of the sand environment where the breeding logs kept during experiment.